LINGUISTIC RACISM IN INDONESIAN CLASROOM CONTEXT: HOW STANDARD ENGLISH MARGINALIZES DIVERSE VOICES - Margaret Stevani; Gus Leonardo Sinabutar; Rendy Bagus Pratama; Heru Widoyo; Alexander Adrian Saragi (Universitas Wiralodra, 2025)
This study investigated linguistic racism in Indonesian EFL classrooms, where Standard English dominated and marginalized regional linguistic identities. Employing Critical Race Theory, raciolinguistics, and postcolonial applied linguistics, it analyzed observations, interviews, and discourse from three junior high schools in Medan. Findings revealed that regional accents and non-standard grammar were policed, corrected, and ridiculed, fostering internalized hierarchies that equated fluency with whiteness and global prestige. English-only policies and Anglo-American curricular content further silenced diverse voices, perpetuating colonial language gatekeeping. Emotional harm, identity suppression, and peer surveillance exacerbated students’ withdrawal and conformity pressures. Nevertheless, students resisted through translanguaging, code-switching, parody, and peer support, asserting hybrid identities and challenging hegemonic norms. The study called for pedagogical reforms embracing culturally responsive and inclusive approaches that validated multilingualism, dismantled linguistic hierarchies, and promoted equitable English learning. This shift was vital to transform classrooms from sites of exclusion to spaces where diverse linguistic identities were empowered.